Sejarah Dan Perkembangan Wakaf Dalam Islam - Luthfiah Nazmi; Yenni Samri Juliati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The history and development of waqf in Islam is a reflection of the deep social, humanitarian and religious values in Islamic teachings. Over the course of its history, waqf has become one of the main pillars of Islamic civilization, making a significant contribution to the development of education, health, culture and social services throughout the Muslim world. This research uses a descriptive method with a qualitative approach based on data sources from literature studies and observations. The aim of this research is to provide information regarding the history and development of waqf. The results of the research explain that waqf already existed during the time of the Prophet and then during the time of Khulafaur Rasyidin, the Islamic Dynasties. As well as the development of the waqf era in various countries.